DEVELOPMENT OF ANDROID-BASED MATHEMATICS LEARNING MEDIA ASSISTED BY ISPRING SUITE 9 AND POWERPOINT TO IMPROVE PROBLEM SOLVING ABILITY - Afidatuzzaro, Nurul; Nirmala, Hidayatul Livia; Fa'ani, Arini Mayan; Putri, Inge Septianing (Math Educa Journal, 2024)
Development of digital-era force teaching and learning situation to have a technology innovation, also in teaching and learning mathematics. Mathematics include an abstract object, so it needs to innovate learning media and learning model to connect from an abstract object to concrete or contextual object so that students can easily understand mathematics. The fact that students’ problem solving skills is still low can be reduced by using appropriate media learning that suitable with students’ characteristics and technology development. This research aims to develop Android-based mathematics learning media with a contextual approach to material on systems of linear equations in two variables (SPLDV) that is valid and practical, and effective in improving students' problem solving abilities. The method used in this research is the ADDIE method (Analyze, Design, Development, Implementation and Evaluation). This research produced a product in the form of Android-based mathematics learning media called MO SPLDV which was categorized as valid with a percentage of 78.378% and the practicality level of the product was obtained in the very practical category with a percentage of 90.42%. This product is effective in improving students' problem solving abilities based on the results of the N-Gain calculation which shows g = 0.5 which is classified as medium.